A multistate trial of pharmacy syringe purchase. - Compton, Wilson M; Horton, Joe C; Cottler, Linda B; Booth, Robert; Leukefeld, Carl G; Singer, Merrill; Cunningham-Williams, Renee; Reich, Wendy; Fortuin Corsi, Karen; Staton, Michele; Fink, Joseph L; Stopka, Thomas J; et al. (Journal of urban health : bulletin of the New York Academy of Medicine, 2004)
Pharmacies are a potential site for access to sterile syringes as a means for preventing human immunodeficiency virus (HIV), but the type and extent of their utility is uncertain. To examine pharmacy syringe purchase, we conducted a standardized, multistate study in urban and rural areas of four states in which attempts to purchase syringes were documented. Of 1,600 overall purchase attempts, 35% were refused. Colorado (25%) and Connecticut (28%) had significantly lower rates of refusal than Kentucky (41%) and Missouri (47%). Furthermore, urban settings had higher rates of refusal (40%) than rural settings (31%, P < .01). Race and gender did not have a consistent impact on rates of refusal. Despite potential advantages of pharmacies as sites for access to sterile syringes, pharmacy purchase of syringes faces significant obstacles in terms of the practices in different jurisdictions.
Keywords: Commerce; Female; HIV Infections; Humans; Male; Pharmacies; Questionnaires; Substance-Related Disorders; Syringes; United States